The Role of Digital Technology in Developing the Study of Falak in Islamic Civilization - Qulub, Siti Tatmainul; Munif, Ahmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Digital technology’s development significantly impacted various aspects of human life, including the study of Falak (Islamic astronomy). This article aims to explain the role of digital technology in developing science in Islamic civilization using a qualitative approach. In Islamic civilization, the science of Falak had a vital role in religious practice. Among them, it helps determine the direction of Qibla, prayer times, calendars, and various celestial phenomena related to religious practices, such as eclipses. The existence of digital technology in the study of Falak includes scientific calculators that help calculations quickly and accurately (replacing rubu’ mujayyab), telescopes that help hilal observations become more precise (replacing the location goal), and theodolite that helps determine the direction of Qibla to be more accurate (replacing compasses and rubu’ mujayyab). Currently, digital technology in science has also developed. It helps remote observation, such as the Dawn Observation Automation System (SOOF) technology to observe Fajar Sadiq and the Hilal Remote Observatory (HRO) to observe the moon from a distance. In addition, science applications/software make science information easier and faster accessible to the public. Thus, the critical role of digital technology in the study of Falak is to help collect data and access information more easily, quickly, and precisely; and provide more detailed and accurate results.